ANALISIS KESTABILAN LUBANG BUKAAN BERDASARKAN KLASIFIKASI GEOMEKANIKA PADA TAMBANG BAWAH TANAH CV. TAHITI COAL, KOTA SAWAHLUNTO, SUMATERA BARAT - Ika Desmawita; Raimon Kopa; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2018)
The excavation of a tunnel in rock mass resulting a change in the balance of rock conditions such as the occurrence of rock collapse and changes in the dimensions of tunnel at the tail gate THC-02 as a result of the displacement of the voltage distribution. It is desirable to have a good geotechnical analysis to provide an appropriate treatment of rocks excavated. This research was conducted to determine rock mass class, rock strength, and stability of open aperture based on potential of wedge collapse by estimating value of Safety Factor (FK) of openings and recommendation of ground support at tail gate hole THC-02 branch C-6.Classification of rocks mass with RMR system and FK potential of wedge using unwadge software. From the measurement of several parameters of RMR method, the average RMR value of 45,3 is obtained whereas rock mass class III (fair rock). From RMR value also obtained the maximum span value of tunnel is 3 m with collapse time 90 hours and collapsed load value 3.705 kg/ m2. The kinematic potential of wedge at the tail gate THC-02 branch C-6 in three general direction joint set with strike/ dip value: N1740E / 790, N1410E / 260, N1600E / 590 where FK value is 9,525 and the wedge stable.Based on the data it can be recommended as follows: if using rock bolt required rock bolt (20 mm diameter, fully grouted) with length 4 m spacing between 1,5-2,0 m bolt on the wall and roof and added wiremesh mounted systematically, 50-100 mm thick shotcrete installation on the roof and 30 mm on the wall, if wooden support required wood 20 cm diameter, length 2 m, grade III (360 kg / cm2) and spacing 1,5 m.